Penerapan Asuhan Keperawatan dengan Intervensi Brain Gym Exercise untuk Mengatasi Masalah Demensia pada Lansia di RW 08, Kelurahan Grogol Utara - Hillalia Nurseha (2022)
Elderly are individuals with advanced age who are individuals with an age exceeding 60 years and over. Elderly is not a disease, but the elderly is an advanced stage of the life process which is characterized by a decrease in the body's ability to adapt to environmental stress. Dementia is a decrease in intellectual function that makes sufferers experience problems in carrying out daily activities, including socializing in their sphere of life. Activity training for the elderly is an activity carried out in a fun way to stimulate the brain so that the elderly are able to participate actively and productively, develop the quality of the elderly and the surrounding environment and prevent the stage of decline in intellectual function or the process of decreasing mindset. Brain exercise is one of the activities that can be carried out regularly so that a person stays fresh and fit. The purpose of this study was to determine the effectiveness of brain gym exercise intervention in overcoming dementia in the elderly. The provision of brain gym exercise intervention was carried out on two elderly people in RW 08 who had impaired cognitive function. The implementation of the brain gym exercise intervention was carried out on March 20-26, 2022 and was carried out for a duration of 30 minutes for each meeting. The results of the implementation of brain gym exercise showed that after the intervention was carried out three times, the elderly experienced an increase in the MMSE score (cognitive function assessment). Community nurses are expected to be able to use brain gym exercise in overcoming the problem of dementia in the elderly.